Assessing mercury concentration in amphibians and reptiles near artisanal gold mining sites in Saweak Village, Lebong Regency, Bengkulu, Indonesia - Vestidhia Y Atmaja; Aldy Riau Wansyah Hasibuan; Deni Parlindungan; Eti Widya Lestari; Cindy Fadli Wulandari Hutabarat; Desy Millenia Ramadhany (BRIN Publishing (Penerbit BRIN), 2026)
Traditional gold mining activities are widespread in various regions of Indonesia, including Bengkulu Province. Many of these operations are unlicensed, resulting in inadequate supervision and poor waste management. Mercury is one of the most common pollutants produced by artisanal mining. This study aimed to determine the diversity of reptile species and analyze mercury accumulation in keratin samples obtained from reptiles inhabiting Saweak Mining Village, Pinang Belapis District, Lebong Regency. Sampling was conducted along river sections in Saweak Village suspected to be contaminated by mercury waste. Herpetofauna were surveyed using the Visual Encounter Survey (VES) method combined with transects during their active periods, both diurnal (08:00-11:00) and nocturnal (19:00-22:00). Collected specimens were identified and analyzed for mercury content. A total of nine herpetofaunal species were recorded, consisting of six amphibians and four reptiles. Mercury concentrations varied among species, with the highest to lowest levels observed in the following order: Wijayarana sumatrana (AMP LB31), W. sumatrana (AMP LB16), Odorrana hosii (AMP LB26), Chalcorana chalconota (AMP LB30), Hylarana chalconota (AMP LB12), Phrynoidis aspera, Megophrys nasuta, O. hosii (AMP LB11), and Fejervarya limnocharis. The highest mercury level (3,073.19 µg/kg) was detected in Odorrana hosii, while the lowest (240.40 µg/kg) was found in Fejervarya limnocharis. These findings indicate that mercury contamination in the study area is pervasive and has been transferred across trophic levels, affecting both aquatic and terrestrial herpetofauna. This highlights the potential ecological risk of mercury pollution and supports the use of herpetofauna as effective biomonitors of long-term environmental contamination.